Membrane Fluidity and Temperature Sensing Are Coupled via Circuitry Comprised of Ole1, Rsp5, and Hsf1 in Candida albicans - Leach, Michelle D. (American Society for Microbiology, 2014)
Temperature is a ubiquitous environmental variable which can profoundly influence the physiology of living cells as it changes over time and space. When yeast cells are exposed to a sublethal heat shock, normal metabolic functions become repressed and the heat shock transcription factor Hsf1 is activated, inducing heat shock proteins (HSPs). Candida albicans, the most prevalent human fungal pathogen, is an opportunistic pathogen that has evolved as a relatively harmless commensal of healthy individuals. Even though C. albicans occupies thermally buffered niches, it has retained the classic heat shock response, activating Hsf1 during slow thermal transitions such as the increases in temperature suffered by febrile patients. However, the mechanism of temperature sensing in fungal pathogens remains enigmatic. A few studies with Saccharomyces cerevisiae suggest that thermal stress is transduced into a cellular signal at the level of the membrane. In this study, we manipulated the fluidity of C. albicans membrane to dissect mechanisms of temperature sensing. We determined that in response to elevated temperature, levels of OLE1, encoding a fatty acid desaturase, decrease. Subsequently, loss of OLE1 triggers expression of FAS2, encoding a fatty acid synthase. Furthermore, depletion of OLE1 prevents full activation of Hsf1, thereby reducing HSP expression in response to heat shock. This reduction in Hsf1 activation is attributable to the E3 ubiquitin ligase Rsp5, which regulates OLE1 expression. To our knowledge, this is the first study to define a molecular link between fatty acid synthesis and the heat shock response in the fungal kingdom.